Method for detecting and analyzing residual stress of thread sheath of continuous fiber reinforced metal matrix composite fastener
By combining nano-indentation technology and X-ray diffraction method, the residual stress of the threaded sleeve of the continuous fiber-reinforced metal-based composite fastener is directly detected, which solves the problem that is difficult to detect in the existing technology, and achieves high-precision stress analysis and distribution research.
Patent Information
- Application Number
- CN202411707341.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to directly detect residual stresses in threaded sleeves of continuous fiber reinforced metal-based composite fasteners, especially in the case of complex tooth structures at the threaded part.
Using a detection and analysis method combined with nanoindentation technology and X-ray diffraction method, the residual stresses in the radial and axial directions were measured respectively by indentation testing on the section of the threaded sleeve and XRD testing on the microcurved surface of the screw tip.
High-precision detection of residual stress of fastener thread cover is achieved, breaking the limitations of conventional detection mode, and can analyze the stress distribution near the surface of the screw teeth, and compare the stress at a certain distance from the top of the screw teeth, and study the influence of different core sizes of composite materials on the residual stress of threads.
Smart Images

Figure CN119509766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal matrix composite materials, and in particular to a method for detecting and analyzing residual stress of a thread sheath of a continuous fiber reinforced metal matrix composite fastener. Background Art
[0002] Continuous fiber reinforced metal matrix composites have the advantages of high plasticity, high damage tolerance and easy processing of the metal matrix as well as light weight, high strength, high stiffness and a wide service temperature range of the fiber. They are favored by engine and hypersonic aircraft designers from various countries and are considered to be essential high-temperature structural materials and potential application materials for connection components of hypersonic aircraft.
[0003] However, during the preparation of composite materials, residual stress is easily generated inside the composite materials due to the difference in thermal expansion between the fiber and the matrix. In addition, during the processing and manufacturing of mechanical parts, residual stress will be generated inside most parts due to the influence of the manufacturing process.
[0004] Taking continuous fiber reinforced metal matrix composite threaded fasteners as an example, due to its unique structural characteristics, in order to ensure the integrity of its internal fiber structure, the thread can only be formed by turning. During the processing, the turning outer diameter, thread spindle speed, feed speed, number of passes, etc. will cause residual plastic deformation on the thread surface, uneven thermal expansion and contraction, and metal structure phase change expansion. These factors will have an important impact on the quality of the thread. When these factors disappear, the effects and influences on the thread structure cannot disappear with them. Some effects and influences still remain in the form of residual stress inside the component. Higher residual stress will deteriorate the mechanical properties of the component. Therefore, measuring the size and distribution of residual stress is of great significance to extending the service life of the component and improving the preparation process.
[0005] Residual stress measurement technology can be divided into two types: destructive measurement method and non-destructive measurement method, depending on whether the test method will cause damage to the tested object. The main principle of the destructive measurement method is to partially separate the component to release stress. Commonly used methods include drilling method, stripping method, peeling method, and ring strain release method. The non-destructive method mainly uses some non-destructive detection methods to measure the residual stress of the material, including synchrotron radiation method, neutron diffraction method, etc.
[0006] At present, the more mature residual stress analysis methods in structural parts are drilling method and X-ray diffraction method. The drilling method generally involves drilling a small hole on the surface of the workpiece, so that the stress around the hole is released, thereby generating corresponding displacement and strain, and then pasting a strain gauge for measurement, and finally obtaining the average residual stress in the depth direction of the hole. The drilling method generally tests a minimum diameter of 0.5mm and a drilling depth of 2mm. The X-ray diffraction method uses the diffraction effect of X-rays in crystalline materials to analyze the material structure. Before the test, the size and surface of the workpiece to be tested must be specially processed, and the surface of the workpiece must be flat and smooth to ensure effective diffraction of the X-rays. Considering the factors such as the tooth structure, pitch and measurement accuracy of the threaded part, it is difficult to directly drill holes in the threaded part. Therefore, it is difficult to directly apply the drilling method and X-ray diffraction method to measure the residual stress in the threaded part. Therefore, how to detect the residual stress of the thread sleeve of continuous fiber reinforced metal matrix composite fasteners has become the focus of research and a technical problem that needs to be solved urgently. Summary of the invention
[0007] The present invention provides a method for detecting and analyzing residual stress of a thread sheath of a continuous fiber reinforced metal matrix composite fastener. The method can detect and analyze residual stress of a thread sheath of a continuous fiber reinforced metal matrix composite fastener.
[0008] The present invention provides a method for detecting and analyzing residual stress of a thread sheath of a continuous fiber reinforced metal matrix composite fastener, comprising the following steps:
[0009] (1) cutting the thread of a continuous fiber reinforced metal matrix composite fastener radially to obtain a cross section of the thread sheath;
[0010] Performing indentation testing and analysis on the section to obtain the nature and magnitude of the radial residual stress of the thread sheath;
[0011] (2) performing XRD testing and analysis on the micro-curved surface at the top of the thread to obtain the nature and magnitude of the axial residual stress of the thread sleeve;
[0012] There is no order of precedence for steps (1) to (2).
[0013] Preferably, before the indentation test, the method further includes: polishing the cut surface.
[0014] Preferably, the indentation test and analysis of the section in step (1) comprises the following steps:
[0015] Performing an indentation test on the section, performing AFM analysis on the obtained indentation to obtain the side length, height and indentation depth of the indentation, and then calculating the indentation area based on the side length and height;
[0016] If the indentation depth is less than the indentation depth of the standard sample, the radial residual stress of the thread sheath is a compressive stress, and the calculation formula of the compressive stress is formula (1):
[0017]
[0018] If the indentation depth is greater than the indentation depth of the standard sample, the radial residual stress of the thread sheath is tensile stress, and the calculation formula of the tensile stress is formula (2):
[0019]
[0020] In formula (1) and formula (2), H is the hardness of the standard sample, A0 is the indentation area of the standard sample, A is the indentation area of the cut surface, and α is the angle between the indenter and the cut surface.
[0021] Preferably, the number of test points during the indentation test is ≥ 2;
[0022] The spacing between adjacent test points and the spacing between the top of the section and the adjacent test points at the top are independently 30 to 150 μm.
[0023] Preferably, the XRD test and analysis of the micro-curved surface at the top of the screw thread in step (2) comprises the following steps:
[0024] At different inclination angles Ψ, the micro-curved surface is scanned by X-ray to obtain the 2θ corresponding to the same specific diffraction peak at different inclination angles Ψ, and then 2θ and sin 2 Ψ is linearly fitted to obtain the slope M;
[0025] Calculate the magnitude of the axial residual stress of the thread sleeve according to formula (3) and formula (4);
[0026]
[0027] In formula (3) and formula (4), E is the elastic modulus of the material, ν is the Poisson's ratio of the material, and θ0 is the Bragg angle corresponding to the specific diffraction peak when there is no stress;
[0028] The σ φ is negative, the nature of the axial residual stress of the thread sleeve is compressive stress; the σ φ is positive, and the nature of the axial residual stress of the thread sleeve is tensile stress.
[0029] Preferably, the scanning angle range during the scanning is 2θ0±3 to 10°, the scanning step length is 0.005 to 0.02°, and the scanning step speed is 0.1 to 0.4 s / step;
[0030] The 2θ0 is between 90 and 130°;
[0031] The 2θ0 is the diffraction angle corresponding to the specific diffraction peak when the thread sheath is stress-free.
[0032] Preferably, the number of the different inclination angles is 4 to 6; and the angles of the different inclination angles are selected within the range of 0 to 80°.
[0033] Preferably, the method for preparing the continuous fiber reinforced metal matrix composite fastener comprises the following steps:
[0034] The metal coated fiber is placed in a metal alloy sheath and then hot isostatically pressed for processing.
[0035] Preferably, the fibers include one or more of SiC fibers, B fibers and Al2O3 fibers.
[0036] Preferably, the material of the metal alloy sheath includes Ti alloy, Ni alloy, Al alloy, Zr alloy or Cu alloy.
[0037] The detection and analysis method proposed in the present invention combines nano-indentation technology and X-ray diffraction to realize the analysis of the residual stress of the fastener thread sheath, breaking the conventional drilling method and X-ray diffraction detection mode, and can realize the radial residual stress analysis of the near-surface part of the thread on a specific section, solving the difficulty of analyzing the residual stress of the fastener thread and improving the residual stress detection accuracy. The results of the embodiment show that the detection and analysis method provided by the present invention can not only analyze the radial and axial residual stress near the surface of the thread, but also compare the residual stress at a certain distance from the top of the thread and analyze the influence of different core sizes (or different wall thicknesses) of composite materials on the residual stress of the thread.
[0038] The present invention provides the above-mentioned method for analyzing residual stress of thread sheath of continuous fiber reinforced metal matrix composite fastener, which is of great significance for residual stress analysis of thread sheath of continuous fiber reinforced metal matrix composite fastener. In addition, the method provided by the present invention is simple to operate, the result is highly accurate (the conventional thread residual stress detection method is for homogeneous materials, a 2mm hole is drilled at the thread, the stress around the hole is released, and the strain change around the hole is measured at the same time, so as to infer the residual stress inside the material, and the result is the average stress of the whole workpiece. The method provided by the present invention adopts indentation method and X-ray method to directly measure the residual stress of the thread part, which can realize the characterization analysis of residual stress at a specific position, has high position accuracy, and can realize stress analysis in a micron-level area), and has the characteristics of strong repeatability and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the detection and analysis method of the present invention;
[0040] Figure 2 This is a SEM image of one of the indentations of the standard sample in Example 1;
[0041] Figure 3 This is an AFM image of one of the indentations of the standard sample in Example 1;
[0042] Figure 4 is the indentation depth curve of the standard sample in Example 1;
[0043] Figure 5 AFM images of indentations a, b, and c in Example 1;
[0044] Figure 6 is the depth curve of the indentations a, b, and c in Example 1;
[0045] Figure 7 This is the X-ray diffraction result diagram in Example 1;
[0046] Figure 8 is the X-ray diffraction result 2θ-sin in Example 1 2 Ψ linear fitting plot;
[0047] Fig. 9 AFM images of indentations a, b, and c in Example 2;
[0048] Fig.10 is the depth curve of the indentations a, b, and c in Example 2;
[0049] Fig.11 This is the X-ray diffraction result diagram in Example 2;
[0050] Fig.12 is the X-ray diffraction result 2θ-sin in Example 2 2 ΨLinear fit plot. DETAILED DESCRIPTION
[0051] The present invention provides a method for detecting and analyzing residual stress of a thread sheath of a continuous fiber reinforced metal matrix composite fastener, comprising the following steps:
[0052] (1) cutting the thread of a continuous fiber reinforced metal matrix composite fastener radially to obtain a cross section of the thread sheath;
[0053] Performing indentation testing and analysis on the section to obtain the nature and magnitude of the radial residual stress of the thread sheath;
[0054] (2) performing XRD testing and analysis on the micro-curved surface at the top of the thread to obtain the nature and magnitude of the axial residual stress of the thread sleeve;
[0055] There is no order of precedence for steps (1) to (2).
[0056] In the present invention, the method for preparing the continuous fiber reinforced metal matrix composite fastener preferably comprises the following steps:
[0057] The metal coated fiber is placed in a metal alloy sheath and then hot isostatically pressed for processing.
[0058] In the present invention, the material of the metal alloy sheath includes Ti alloy, Ni alloy, Al alloy, Zr alloy or Cu alloy; when the continuous fiber reinforced metal matrix composite fastener is a MJ6×1 thread, the inner diameter of the metal alloy sheath is preferably ≤4mm, and the outer diameter is preferably ≥6mm; when the continuous fiber reinforced metal matrix composite fastener is a MJ10×1.25 thread, the inner diameter of the metal alloy sheath is preferably ≤7mm, and the outer diameter is preferably ≥10.5mm.
[0059] In the present invention, the method for preparing the fiber coated with the metal coating preferably comprises the following steps:
[0060] The metal is deposited on the fiber surface by PVD technology.
[0061] The present invention has no special limitation on the parameters of the PVD deposition, and any method known to those skilled in the art may be used.
[0062] In the present invention, the thickness of the metal coating is preferably 20-25 μm. In a specific embodiment of the present invention, the thickness of the metal coating may be 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm.
[0063] The material of the metal coating is preferably consistent with the material of the sheath material; the fibers preferably include one or more of SiC fibers, B fibers and Al2O3 fibers.
[0064] During hot isostatic pressing, the metal coating is in a nearly molten state and can spontaneously flow to fill the gaps and form a dense structure.
[0065] In the present invention, the hot isostatic pressing conditions are specifically set according to different alloy sheaths. Taking Ti alloy as an example, the hot isostatic pressing temperature is preferably 980° C., the time is preferably 2 h, and the pressure is preferably 150 MPa.
[0066] In the present invention, the indentation test and analysis of the cut surface in step (1) preferably includes the following steps:
[0067] An indentation test is performed on the section, and the obtained indentation is analyzed by AFM to obtain the side length, height and indentation depth of the indentation, and then the indentation area is calculated based on the side length and height.
[0068] Before the indentation test, the method preferably further comprises: polishing the cut surface. The present invention has no special limitation on the polishing, and the polishing to a mirror surface can be performed using a technical solution known to those skilled in the art.
[0069] In the present invention, the number of test points in the indentation test is ≥ 2, and the spacing between connected test points and the spacing between the top of the cut surface and the test point adjacent to the top are preferably independently 30 to 150 μm. In a specific embodiment of the present invention, the spacing between connected test points and the spacing between the top of the cut surface and the test point adjacent to the top during the indentation test can be independently 30 μm, 50 μm, 80 μm, 100 μm, 120 μm or 150 μm; the test points are preferably on a straight line connecting the center of the fastener and the edge of the fastener.
[0070] In the present invention, the indentation depth set during the indentation test is preferably 0.5-2 μm. In a specific embodiment of the present invention, the set indentation depth can be 0.5 μm, 1 μm, 1.5 μm or 2 μm.
[0071] After performing AFM analysis on the obtained indentation, the present invention preferably obtains the length of each side of the indentation and the corresponding height, and then calculates the indentation area corresponding to each side, and then takes the average value to calculate the final indentation area.
[0072] If the indentation depth is less than the indentation depth of the standard sample, the radial residual stress of the thread sheath is a compressive stress, and the calculation formula of the compressive stress is formula (1):
[0073]
[0074] If the indentation depth is greater than the indentation depth of the standard sample, the radial residual stress of the thread sheath is tensile stress, and the calculation formula of the tensile stress is:
[0075]
[0076] H is the hardness of the standard sample, A0 is the indentation area of the standard sample, A is the indentation area of the cut surface, and α is the angle between the indenter and the cut surface.
[0077] In the present invention, the XRD test and analysis of the micro-curved surface at the top of the screw thread in step (2) preferably includes the following steps:
[0078] At different inclination angles Ψ, the micro-curved surface is scanned by X-ray to obtain the 2θ corresponding to the specific diffraction peaks at different inclination angles Ψ, and then 2θ and sin 2 Ψ is fitted linearly to obtain the slope M.
[0079] Before the X-ray scanning, the present invention preferably performs fine adjustment on the micro-curved surface.
[0080] The present invention has no special limitation on the fine-tuning, and the fine-tuning may be performed until an obvious diffraction peak appears.
[0081] In the present invention, the scanning angle range during the scanning is preferably 2θ0±3~10°. In a specific embodiment of the present invention, the scanning angle range can be 2θ0±2~8°, 2θ0±4~6° or 2θ0±3~10°; in the present invention, the 2θ0 is preferably 90~130°; the diffraction angle corresponding to the specific diffraction peak when the thread sheath is stress-free.
[0082] In the present invention, the scanning step size during the scanning is preferably 0.005-0.02°. In a specific embodiment of the present invention, the scanning step size may be 0.005°, 0.01°, 0.015° or 0.02°. The scanning step speed is 0.1-0.4s / step. In a specific embodiment of the present invention, the scanning step speed may be 0.1s / step, 0.2s / step, 0.3s / step or 0.4s / step.
[0083] In the present invention, the number of the different inclination angles is preferably 4 to 6. In a specific embodiment of the present invention, the number of the different inclination angles can be 4, 5 or 6. The angles of the different inclination angles are selected within the range of 0 to 80°. In a specific embodiment of the present invention, the angles of the inclination angles can be 0°, 15°, 30°, 45°, 50°, 60°, 75° or 80°. The inclination angle refers to the rotation inclination angle of the thread segment.
[0084] After obtaining the slope M, the present invention calculates the magnitude of the axial residual stress of the thread sleeve according to formula (3);
[0085]
[0086] E is the elastic modulus of the material, ν is the Poisson's ratio of the material, and θ0 is the Bragg angle corresponding to the specific diffraction peak when there is no stress;
[0087] The σ φ is negative, the nature of the axial residual stress of the thread sleeve is compressive stress; the σ φ is positive, and the nature of the axial residual stress of the thread sleeve is tensile stress.
[0088] Figure 1 Schematic diagram of the detection and analysis method of the present invention.
[0089] The following is a detailed description of the method for detecting and analyzing the residual stress of the thread sheath of the continuous fiber reinforced metal matrix composite fastener provided by the present invention in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0090] In the embodiment, α=24.7°
[0091] Example 1
[0092] The fiber is SiC fiber, the matrix is Ti3Al, and the core size is 3mm.
[0093] 1. Analysis of radial residual stress using nanoindentation method:
[0094] 1) The Ti3Al alloy was heat treated at 980℃ / 2h to obtain a standard sample, which was then electropolished to a mirror surface. Nine points on the surface were randomly selected for indentation testing using the nanoindentation method. The indentation depth was set to 1μm, and the average hardness of the nine points was H=4.76Gpa.
[0095] Figure 2 This is the SEM image of one of the indentations of the standard sample;
[0096] Figure 3 This is the AFM image of one of the indentations of the standard sample;
[0097] The indentation area was calculated by 1 / 2Lh in the AFM morphology, and the average value was A0 = 16.35 μm 2 .
[0098] Figure 4 is the indentation depth curve of the standard sample.
[0099] Depend on Figure 4 It can be seen that the deepest indentation of the standard sample is 750nm. When the thread is subjected to an indentation test, if the depth is less than 750nm, it is considered that the thread matrix is under compressive stress, and if the depth is greater than 750nm, it is considered that the thread matrix is under tensile stress.
[0100] 2) A 25 μm thick Ti3Al coating was deposited on the surface of SiC fiber (100 μm in diameter) by PVD to obtain a precursor wire, which was packaged in a Ti3Al sheath with an inner diameter of 3 mm and a thickness of 2 mm in a bundle shape, and hot isostatically pressed at 980°C / 150 MPa / 2 h to obtain a continuous SiC fiber reinforced Ti3Al composite material (SiC f / Ti3Al), and the composite material was turned into MJ6 bolts at a turning speed of 400r / min.
[0101] 3) According to Figure 1 The threaded section of the bolt was cut radially to obtain the cross section of the thread and then electropolished. Three points a, b, and c were taken radially at a distance of 100 nm from the top of the tooth for nanoindentation, with a point spacing of 100 nm.
[0102] Figure 5 AFM images of indentations a, b, and c; Figure 6Depth curve of indentations a, b, and c.
[0103] The areas of the three indentation points a, b, and c are 15.92 μm 2 、16.09μm 2 、16.10μm 2 From the depth curve, we can see that the depths of the three points are all less than 750nm, indicating that the three points are under compressive stress. Substituting into the compressive stress calculation formula, we can get the residual compressive stresses of points a, b, and c, respectively, which is -307MPa, -184MPa, and -175MPa, indicating that SiC f The residual stress near the surface of the thread of the / Ti3Al bolt is compressive stress, and the closer to the top of the thread, the greater the residual compressive stress.
[0104] 2. Use X-ray diffraction method to analyze axial residual stress:
[0105] 1) When performing X-ray diffraction measurement, the sample should be fine-tuned to ensure that the X-ray can detect the micro-curved surface at the top of the screw thread. The sample inclination angle Ψ was selected at four angles: 0°, 15°, 30°, and 45°. The diffraction peaks selected were Ti3Al, 2θ (204) =94.38° high-angle diffraction peak, scanning step length of 0.01°, step speed of 0.2s / step, scanning starting angle of 2θ (204) =92°, the end angle is 2θ (204) =96°.
[0106] 2) The results of X-ray diffraction are as follows Figure 7 As shown, the X-ray diffraction results were subjected to 2θ-sin 2 Ψ linear fitting, the result is as follows Figure 8 shown.
[0107] Substituting the fitted slope into equation (3) yields SiC f / Ti3Al bolt fastener thread top axial residual stress is -387.6MPa, the residual stress value is negative, indicating that SiC f The axial compressive stress of the / Ti3Al bolt thread is 387.6MPa.
[0108] From the calculation results, it can be seen that the analysis method of the present invention can not only analyze the radial and axial residual stress distribution near the thread sleeve tooth top surface, but also can compare the residual stress size at a certain distance from the thread top.
[0109] Example 2
[0110] The fiber is SiC fiber, the matrix is Ti3Al, and the core size is 4mm.
[0111] 1. Analysis of radial residual stress using nanoindentation method:
[0112] 1) The preparation and parameters of the standard sample were consistent with those in Example 1.
[0113] 2) A 25 μm thick Ti3Al coating was deposited on the surface of SiC fiber (diameter 100 μm) by PVD to obtain a precursor wire, which was packaged in a Ti3Al sheath with an inner diameter of 4 mm and a thickness of 1 mm in the form of a bundle of wires, and hot isostatically pressed at 980°C / 150 MPa / 2 h to obtain a continuous SiC fiber reinforced Ti3Al composite material, which was then machined into MJ6 bolts by turning.
[0114] 3) According to Figure 1 The thread section of the bolt was cut radially to obtain the cross section of the thread and polished. Three points a, b, and c were taken radially at a distance of 100 nm from the top of the tooth for nanoindentation. The point spacing was 100 nm.
[0115] Fig. 9 AFM images of indentations a, b, and c; Fig.10 Depth curve of indentations a, b, and c.
[0116] The areas of the three indentation points a, b, and c are 15.63 μm 2 、15.74μm 2 、15.93μm 2 From the depth curve, we can see that the depths of the three points are all less than 750nm, indicating that the three points are under compressive stress. Substituting into the compressive stress calculation formula, we can get the residual compressive stresses of points a, b, and c, respectively, which are -527MPa, -446MPa, and -297MPa, indicating that SiC f The residual stress near the surface of the thread of the / Ti3Al bolt is compressive stress, and the closer to the top of the thread, the greater the residual compressive stress.
[0117] 2. Use X-ray diffraction method to analyze axial residual stress:
[0118] 1) When performing X-ray diffraction measurement, the sample should be fine-tuned to ensure that the X-ray can detect the micro-curved surface at the top of the screw thread. The sample inclination angle Ψ was selected at four angles: 0°, 15°, 30°, and 45°. The diffraction peaks selected were Ti3Al, 2θ (204) =94.38° high-angle diffraction peak, scanning step length of 0.01°, step speed of 0.2s / step, scanning starting angle of 2θ (204) =92°, the end angle is 2θ (204) =96°.
[0119] 2) The results of X-ray diffraction are as follows Fig.11As shown, the X-ray diffraction results were subjected to 2θ-sin 2 Ψ linear fitting, the result is as follows Fig.12 shown.
[0120] Substituting the fitted slope into equation (3) yields SiC f / Ti3Al bolt fastener thread top axial residual stress is -540.6MPa, the residual stress value is negative, indicating that SiC f / Ti3Al bolt thread axial compressive stress is 540.6MPa.
[0121] It can be seen from the calculation results that the analysis method of the present invention can not only analyze the radial and axial residual stresses near the thread crest surface, but also can compare the residual stresses at a certain distance from the thread crest.
[0122] Combining Example 1 and Example 2, it can be seen that the analysis method of the present invention can be used to study the radial and axial residual stresses at the top of the screw thread, and can also be used to compare the residual stresses at a certain distance from the top of the screw thread. At the same time, it can also be used to compare the influence of different core sizes (or different wall thicknesses) of the composite material on the residual stress of the thread.
[0123] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for detecting and analyzing residual stress of thread sheath of continuous fiber reinforced metal matrix composite fastener, characterized in that: The following steps are involved: (1) cutting the thread of a continuous fiber reinforced metal matrix composite fastener radially to obtain a cross section of the thread sheath; Performing indentation testing and analysis on the section to obtain the nature and magnitude of the radial residual stress of the thread sheath; (2) performing XRD testing and analysis on the micro-curved surface at the top of the thread to obtain the nature and magnitude of the axial residual stress of the thread sleeve; There is no order of precedence for steps (1) to (2).
2. The detection and analysis method according to claim 1, characterized in that: Before the indentation test, the method further includes: polishing the cut surface.
3. The detection and analysis method according to claim 1 or 2, characterized in that: The step (1) of performing an indentation test and analysis on the section includes the following steps: Performing an indentation test on the section, performing AFM analysis on the obtained indentation to obtain the side length, height and indentation depth of the indentation, and then calculating the indentation area based on the side length and height; If the indentation depth is less than the indentation depth of the standard sample, the radial residual stress of the thread sheath is a compressive stress, and the calculation formula of the compressive stress is formula (1): If the indentation depth is greater than the indentation depth of the standard sample, the radial residual stress of the thread sheath is tensile stress, and the calculation formula of the tensile stress is formula (2): In formula (1) and formula (2), H is the hardness of the standard sample, A0 is the indentation area of the standard sample, A is the indentation area of the cut surface, and α is the angle between the indenter and the cut surface.
4. The detection and analysis method according to claim 3, characterized in that: The number of test points in the indentation test is ≥ 2; The spacing between adjacent test points and the spacing between the top of the section and the adjacent test points at the top are independently 30 to 150 μm.
5. The detection and analysis method according to claim 1, characterized in that: The step (2) of performing XRD testing and analysis on the micro-curved surface at the top of the screw thread comprises the following steps: At different inclination angles Ψ, the micro-curved surface is scanned by X-ray to obtain the 2θ corresponding to the same specific diffraction peak at different inclination angles Ψ, and then 2θ and sin 2 Ψ is linearly fitted to obtain the slope M; Calculate the magnitude of the axial residual stress of the thread sleeve according to formula (3) and formula (4); In formula (3) and formula (4), E is the elastic modulus of the material, ν is the Poisson's ratio of the material, and θ0 is the Bragg angle corresponding to the specific diffraction peak when there is no stress; The σ φ is negative, the nature of the axial residual stress of the thread sleeve is compressive stress; the σ φ is positive, and the nature of the axial residual stress of the thread sleeve is tensile stress.
6. The detection and analysis method according to claim 5, characterized in that: The scanning angle range during the scanning is 2θ0±3~10°, the scanning step length is 0.005~0.02°, and the scanning step speed is 0.1~0.4s / step; The 2θ0 is between 90 and 130°; The 2θ0 is the diffraction angle corresponding to the specific diffraction peak when the thread sheath is stress-free.
7. The detection and analysis method according to claim 5 or 6, characterized in that: The number of the different inclination angles Ψ is 4 to 6; and the angles of the different inclination angles Ψ are selected within the range of 0 to 80°.
8. The detection and analysis method according to claim 1, characterized in that: The method for preparing the continuous fiber reinforced metal matrix composite fastener comprises the following steps: The metal coated fiber is placed in a metal alloy sheath and then hot isostatically pressed for processing.
9. The detection and analysis method according to claim 8, characterized in that: The fibers include one or more of SiC fibers, B fibers and Al2O3 fibers.
10. The detection and analysis method according to claim 8 or 9, characterized in that: The material of the metal alloy sheath includes Ti alloy, Ni alloy, Al alloy, Zr alloy or Cu alloy.
Citation Information
Patent Citations
Residual stress characterization method for curved surface special-shaped part
CN111664978A
Method for testing laser nick residual stress of oriented silicon steel
CN117451555A
Residual stress estimation method using instrumented indentation technique
KR101373059B1